Fast & Powerful Machine Learning Tools in Engineering - Markou, George; Bakas, Nikolaos P.; Papadopoulos, Vissarion; Papadrakakis, Manolis (My University, 2023)
A set of lectures discussing the state-of-the-art on Fast & Powerful Machine Learning Tools in Engineering.
Keywords: Machine Learning; High Performance Computing; Engineering